Convivial Futures Views from a Post-Growth Tomorrow - Adloff, Frank; Caillé, Alain (X-Texte zu Kultur und Gesellschaft, 2022)
What steps are needed to make life better and more convivial? The Second Convivialist Manifesto (2020) has presented a short diagnosis of the current crises and sketches of a possible and desirable future. It has been a necessary work of theoretical synthesis, but preserving a viable world also requires passion. It is thus urgent to show what people would gain from a shift to a post-neoliberal and post-growth convivialist future. This volume includes a theoretical debate on convivialism which reflects dystopias and shows the multiple and major obstacles that convivialism will have to face. Mainly, however, the contributors to this volume create sketches of a convivial future and collect accounts of another future world which is attractive for as many as possible.